Novel ABCB1 and ABCC Transporters Are Involved in the Detoxification of Benzo(α)pyrene in Thick Shell Mussel, Mytilus coruscus - Guo, Baoying; Xu, Zhongtian; Yan, Xiaojun; Buttino, Isabella; Li, Jiji; Zhou, Chao; Qi, Pengzhi (Frontiers in Marine Science, 2020)
ATP-binding cassette (ABC) transporters play a role in xenobiotic resistance through transporting xenobiotics into or out of cells. However, their functional role in molluscs defense against polycyclic aromatic hydrocarbons (PAHs) remains unclear. In the present study, novel McoABCB1 and McoABCC transporters were identified from the thick shell mussel Mytilus coruscus, and their benzo(α)pyrene (Bap) detoxification function in gills was determined by qRT-PCR and efflux assays. McoABCB1 and McoABCC transcripts were constitutively expressed in all examined tissues, suggesting a primary physiological function. Bap, used as a chemical stress agent, induced expression of McoABCB1 and McoABCC mRNA in gills, however at high concentration, it inhibited their expression at the late stage. Efflux activities in M. coruscus gills showed a dose-dependent elevation in the Bap pre-exposure group, compared with that in the reversin 205 or MK571 single exposure groups. These results demonstrated the presence of two types of ABC transporters and their involvement in cellular Bap detoxification.